Juvenile Institutional Misconduct: examining the Role of Educational Attainment and Academic Achievement - Engstrom, Ronda Shepherd (Crime & delinquency, 2020)
Identifying risk factors of institutional misconduct among juvenile offenders is important in curbing costs and consequences of these infractions. Research shows low educational attainment and poor academic achievement are consistently related to delinquency and crime. Yet, no research has examined whether these educational variables are associated with institutional misconduct among juveniles. Official records and interviews yielded information on the educational characteristics and institutional misconduct of 349 juvenile prisoners in a California facility. Negative binomial regression analysis was employed to examine hypothesized relationships. Results indicate that graduating high school significantly predicts institutional misconduct. Implications for juvenile corrections policies, including the importance of assisting juvenile detainees in obtaining their high school diploma, and directions for future research are provided.